Gender Differences in Child Malnutrition in Ethiopia: Evidence from Three Decomposition Techniques - Meijuan Wang; Denis Nadolnyak; Valentina Hartarska (Research in Applied Economics, 2024)
Ethiopia has one of the highest under-five child mortality rate in the world, which is higher for boys than for girls. Malnutrition is a major contributing factor to child mortality and that is why we assess the differences in child malnutrition status of boys and girls. Specifically, we study the extent to which the gender differences in malnutrition are associated with observable factors and socio-economic characteristics and to what extent these differences are unexplained and attributable to factors such as latent parental preferences, societal biases, and other unobservable factors. We use data from the Ethiopia Demographic and Health Survey and evaluate three anthropometric status measures – wasting, stunting, and being underweight. We utilize a reduced-form demand for nutrition framework and several decomposition techniques: Oaxaca-Blinder decomposition for non-linear models, Machado-Mata quantile decomposition, and the recentered influence function. The results indicate that measurable socioeconomic and locational characteristics have significant and plausible associations with malnutrition by gender. We also find that 3% to 4% of the difference in the anthropometric status may be attributable to unobservable factors that may include implicit parental preferences. This approach is useful in evaluating gender differences in other human capital development outcomes such as health and education, as well as those in malnutrition.